Getting what you want: A compelling, reusable, one-page message. - Martin A Draper; Betsy B Draper (Academic Chairpersons Conference Proceedings, 2018)
Using examples from planning and evaluation, government and business models, presenters will share tactics and strategies for simple, concise communications on important issues. Participants will practice by developing a one-page position paper, briefing paper or decision memo.
Keywords: Effective management; organizational management; results-based management; effective communication